Computational selections of terpenes present in the plant Calotropis gigantea as mosquito larvicides by blocking the sterol carrying protein, AeSCP-2 (Bangladesh Journal of Pharmacology, 2012)
The present study reports the phytochemical properties of Calotropis gigantea (Asclepiadaceae) commonly known as milk weed. In addition, in silico docking analysis was also carried out to assess the mosquito larvicidal potential of three terpene compounds isolated from C. gigantea. Considerable amount of primary metabolites, essential macro and micro nutrients were documented in the plant. The GC-MS analysis of the chloroform extract revealed the presence of eight terpenes in the plant. From the docking studies it is evident that ?-amyrin has a great potential against AeSCP-2. The phytochemical screening and docking results gives strong baseline information for the posterity.